Let g the inverse function of f.
The most important property of g and f being inverses of each other, is that
g(f(x))=x, also f(g(x))=x
so, what one function 'does' to x, the other 'undoes' it.
Thus, we have:
f(g(x))=x and alos f(g(x))= -g(x)+3, from the rule
thus :
-g(x)+3=x
-g(x)=x-3
g(x)=-x+3
check: f(g(x))=f(-x+3)=-(-x+3)+3=x-3+3=x
Answer: the inverse of f is g, such that g(x)=-x+3
Answer:
x+2 is a factor of
Step-by-step explanation:
To check: If (x+2) is a a factor of the polynomial
We need to check if x = -2 is the FACTOR of the given polynomial.
⇒ To show: f (-2) = 0
Now
Since, f(-2) = 0
⇒ -2 is the ROOT of the Polynomial f(x).
⇒(x +2) is the factor of the given polynomial.
Hence, x+2 is a factor of
Answer:
11m + 4n
Step-by-step explanation:
when two numbers with the same variable are added together or subtracted the result is just the numbers added or subtracted. So you can add 6m and 5m to get 11m. and you can subtract 3n from 7n to get 4n
11m + 4n
The average is 2. To find the average you add all the numbers then divide the sum by the total amount of numbers.